Adjuvant Therapy for Pancreatic Cancer - Goodman, Martin D; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Survival for patients with pancreas cancer is correlated to stage. Only 20% of patients present with localized disease amenable to potentially curative resection but, despite resection, the 5-year survival rate for early stage patients remains less than 25%. Current accepted standard of care is adjuvant gemcitabine following curative resection but there have been no conclusions regarding the role or timing of adjuvant chemoradiation. Although systemic disease represents the major risk for failure following resection, there are patients who would benefit from adjuvant local therapy that remain difficult to identify at present. This year at 2014 ASCO Gastrointestinal Cancers Symposium, Cho at al. (Abstract #325) presented the results of adjuvant gemcitabine with the addition of docetaxel followed by 5-FU chemoradiation for patients with resected pancreatic cancer. Kumar et al. (Abstract #330) compared adjuvant chemoradiation to adjuvant chemotherapy. Lastly Heestand et al. (Abstract #176) used a novel way to look at different biomarkers in serum of patients in the RTOG 9407 study and evaluated the survival depending on the type of chemotherapy used. A lower serum CEA and CA 19-9 gave a better overall survival in all patients which has already been established. Low levels of matrix metalloproteinase-7 (MMP-7) predicted an overall survival benefit from adjuvant gemcitabine, but not from 5-FU. Image: Schema of the treatment with gemcitabine plus docetaxel (Figure 1)